Reading material personalization searching in e-learning - Shuib, L.; Normadhi, A.B.A. (2015)
A student’s ability to grasp new concepts or knowledge from reading material is crucial and dependent on their personalization. Personalization can be identified using learning style. In e-learning, identifying learning style, and matching reading material based on learning style, is critical for students; as it may affect their learning progress and their rate of absorbing information. Therefore, it is crucial for students to be able to locate reading material that best matches their particular learning style. The objective of this paper is to develop a tool that can help retrieve reading material based on personalization. By using a collaborative filtering method, this tool will be able to help students locate reading material that best matches their learning style in e-learning. The architecture and components of the tool are discussed.